Callie - Miles, Ellen (New York : Scholastic, 2011)
When Mia finds a tiny, hurt calico kitten foraging for food, she must convince her parents that she is ready for the responsibility of having a cat.
"Where kittens get the love they need"--Cover
RL: 2.3.
007-010.
Guided reading level: O; Lexile: 620L.
Keywords: Calico cats -- Juvenile fiction; Kittens -- Juvenile fiction; Cats -- Juvenile fiction